СРАВНИТЕЛЬНАЯ ОЦЕНКА НАУЧНОЙ ПРОДУКТИВНОСТИ ИССЛЕДОВАТЕЛЬСКИХ УЧРЕЖДЕНИЙ РАН И СЕКТОРА РОССИЙСКОЙ ВЫСШЕЙ ШКОЛЫ ПО НЕКОТОРЫМ БИБЛИОМЕТРИЧЕСКИМ ИНДИКАТОРАМ (2000-2009 гг.) (Библиосфера)
In recent years increasingly one can hear disputes on the quality and impact of scientific researches in Russia in different organizations, which are published in periodicals and Internet. Particularly acute is criticism of academic science which is being opposed to that of a higher school. In this article the authors have attempted to assess the contribution of scientific organizations, working under the Russian Academy of Sciences and higher school on the basis of bibliometric data of publications for the period of 2000 to 2009 presented in Web of Science and Essential Science Indicators by Thomson Reuters.